Quantitative impacts of climate change and human activities on runoff in the Huolin River catchment. Issue 11 (7th November 2022) - Dan, Dan; Xi, Chun; Haijun, Zhou; Zhiqiang, Wan; Yingying, Xia; Na, Wang
Abstract: The Huolin River is located in the monsoon marginal zone in Northeast China. It is an important source of the wetland system on the Northeast Plain. Recently, a dramatic reduction in the observed river runoff has resulted in a record high level of dried-up days in the Huolin River catchment (HRC). In this study, we used the hydrological simulation approach of the Soil and Water Assessment Tool (SWAT) model to evaluate the influences of climate change and human activities on runoff in the HRC. The SWAT model effectively simulated the streamflow changes in the HRC with a high accuracy. The R 2 values were 0.71 and 0.69 for the calibration and validation periods, respectively. In addition, the Nash-Sutcliffe efficiency (NSE) index reached 0.69 and 0.66 for the calibration and validation periods, respectively. The simulation results demonstrated that the variations in runoff have mostly been caused by combined influence of climate change and land use/land cover (LULC) changes, but the contributions of these factors varied in each period. The climate factors contributed 84.5% of runoff fluctuations before 2000, while the effect of LULC changes gradually grew to 63.6% after 2000. The increase in the influence of LULC changes was mainly apparent in the considerable growth of the areas of the arable land and construction land, which increased by 607 and 113 km 2, respectively. This study provides an effective scientific basis for establishing long-term water management in catchment scale and regional social and economic development under the changing environment. HIGHLIGHTS: The SWAT model has strong feasibility and applicability in monthly runoff simulation of the HRC. Climate change played a dominant role in the runoff variation in the HRC before 2000. The decrease in runoff in HRC is the result of a combination of climate change and human activities. Graphical Abstract